Exosomal integrin alpha 3 promotes epithelial ovarian cancer cell migration via the S100A7/p-ERK signaling pathway - Yin Zeyuan; Ma Jiachen; Adu-Amankwaah Joseph; Xie Guangyan; Wang Yinghao; Tai Wei; Sun Zhenquan; Huang Chuting; Chen Guanfeng; Fu Tong; Zhang Bei; Zhou Xueyan (Acta Biochimica et Biophysica Sinica)
Epithelial ovarian cancer (EOC) is a highly aggressive malignancy with a poor prognosis due to late-stage diagnosis and the lack of reliable biomarkers for early detection. Exosomes, small vesicles involved in intercellular communication, play a critical role in cancer progression by promoting migration, proliferation, and metastasis. This study investigates the role of exosomal proteins in EOC cell migration and identifies potential biomarkers. Exosomes are isolated from the ascites fluid of EOC patients (C-Exos) and benign ovarian disease patients (B-Exos), and mass spectrometry analysis of clinical samples reveals 185 differentially expressed proteins, with integrin alpha 3 (ITGA3) being strongly associated with poor prognosis. ITGA3 is transported via exosomes to recipient EOC cells, where it is released into the cytoplasm and translocated to the cell membrane. This localization enables ITGA3 to activate the intracellular signaling pathways that drive EOC migration. Immunoprecipitation mass spectrometry of clinical samples reveals that ITGA3 may influence EOC migration through the S100A7/p-ERK signaling pathway. Mechanistically, ITGA3 activates ERK signaling through S100A7, promoting cell migration. In vivo, exosomes enrich with ITGA3 facilitates tumor growth and migration, whereas ITGA3 knockdown reduces these effects. These findings suggest that exosomal ITGA3, via the S100A7/p-ERK signaling pathway, promotes EOC cell migration. ITGA3 could serve as a prognostic biomarker and therapeutic target in EOC. Targeting the ITGA3/S100A7 axis may help suppress migration, suggesting a promising strategy to improve EOC patient outcomes.